2017
DOI: 10.3390/nu9050500
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient Intake and Risk of Crohn’s Disease: Systematic Review and Dose–Response Meta-Analysis of Epidemiological Studies

Abstract: Dietary intake is potentially associated with the onset of Crohn’s disease (CD), but evidence from epidemiological studies has remained unclear. This study aimed to evaluate the role of macronutrient intake in the development of CD. A systematic search was conducted in PubMed and Web of Science to identify all relevant studies, and the role of macronutrients in the development of CD was quantitatively assessed by dose–response meta-analysis. Four case-control studies (a total of 311 CD cases and 660 controls) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 39 publications
2
38
0
Order By: Relevance
“…A total of 145 meta-analytic estimates were retained for the main analysis: 74 (51%) reported effects that were significant at P < .05 and 32 (22%) at P < .001. The putative environmental factors pertained to lifestyles and hygiene (n ¼ 16), 6,18-30 surgeries (n ¼ 2), exposure to drugs (n ¼ 3), [37][38][39][40][41][42] dietary intake and nutrients (n ¼ 22), [43][44][45][46][47][48][49][50][51][52][53][54][55] and microorganisms and vaccinations (n ¼ 28). [56][57][58][59][60][61][62][63][64][65][66][67][68][69] Quality Assessment of Meta-analyses The AMSTAR 2 rating for all studies was determined to be critically low (31 studies, 60%) or low (21 studies, 40%) (Supplementary Table 4).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 145 meta-analytic estimates were retained for the main analysis: 74 (51%) reported effects that were significant at P < .05 and 32 (22%) at P < .001. The putative environmental factors pertained to lifestyles and hygiene (n ¼ 16), 6,18-30 surgeries (n ¼ 2), exposure to drugs (n ¼ 3), [37][38][39][40][41][42] dietary intake and nutrients (n ¼ 22), [43][44][45][46][47][48][49][50][51][52][53][54][55] and microorganisms and vaccinations (n ¼ 28). [56][57][58][59][60][61][62][63][64][65][66][67][68][69] Quality Assessment of Meta-analyses The AMSTAR 2 rating for all studies was determined to be critically low (31 studies, 60%) or low (21 studies, 40%) (Supplementary Table 4).…”
Section: Search Resultsmentioning
confidence: 99%
“…43 Sucrose intake also was a risk factor for UC (RR, 1.10; 95% CI, 1.02-1.18; per 10-g increment/day) and CD (RR, 1.09; 95% CI, 1.02-1.16; per 10-g increment/day) with evidence of a dose-response relationship (UC: P ¼ .03; CD: P ¼ .02) ( Figure 3 and Supplementary Tables 1 and 2). 44,45 Alcohol and coffee consumption, however, were not associated with UC ( Figure 3). 43 No evidence of associations between carbohydrate, sugar, protein, or fat intake and either UC or CD were noted in metaanalyses that included high-quality studies (Figure 3 and Supplementary Tables 1 and 2).…”
Section: Exposure To Drugsmentioning
confidence: 96%
See 1 more Smart Citation
“…Refined carbohydrates (e.g., sucrose and fructose syrup) are enriched in sugared‐beverages and desserts. Two meta‐analyses found no association between total amount of carbohydrate intake and the risk of IBD, but excessive intake of sucrose was associated with a high risk of both UC and CD . Every 10 g increment in daily intake of sucrose was associated with 10% more likelihood of IBD, of which the possible mechanism was the changes in gut microbiota.…”
Section: Diet In the Pathogenesis Of Ibdmentioning
confidence: 99%
“…Two meta-analyses found no association between total amount of carbohydrate intake and the risk of IBD, but excessive intake of sucrose was associated with a high risk of both UC and CD. 24,25 Every 10 g increment in daily intake of sucrose was associated with 10% more likelihood of IBD, of which the possible mechanism was the changes in gut microbiota. Another systematic review confirmed a positive relationship between sugared beverage consumption and the risk of UC, 26 especially for those with a low intake of vegetables for 2 years (between the highest and lowest quintile: incidence rate ratio 1.68, 95% confidence interval…”
Section: Refined Carbohydratesmentioning
confidence: 99%